# How do you express #cos( (15 pi)/ 8 ) * cos (( 5 pi) /8 ) # without using products of trigonometric functions?

By signing up, you agree to our Terms of Service and Privacy Policy

cos((15π)/8) * cos((5π)/8) can be expressed without using products of trigonometric functions by utilizing the sum-to-product identities. Specifically, we can use the identity cos(A) * cos(B) = (1/2) * [cos(A - B) + cos(A + B)].

Substituting A = (15π)/8 and B = (5π)/8 into this identity, we get:

cos((15π)/8) * cos((5π)/8) = (1/2) * [cos((15π)/8 - (5π)/8) + cos((15π)/8 + (5π)/8)].

Simplify the expressions inside the cosine functions:

(15π)/8 - (5π)/8 = (10π)/8 = (5π)/4

(15π)/8 + (5π)/8 = (20π)/8 = (5π)/2

Now, substitute these values back into the equation:

cos((15π)/8) * cos((5π)/8) = (1/2) * [cos((5π)/4) + cos((5π)/2)].

Using the values of cosine at (5π)/4 and (5π)/2:

cos((5π)/4) = -√2/2

cos((5π)/2) = 0

Substitute these values into the equation:

(1/2) * [-√2/2 + 0]

Simplify the expression:

= -(√2)/4.

Therefore, cos((15π)/8) * cos((5π)/8) = -(√2)/4.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you factor and simplify #sin^4x-cos^4x#?
- How do you solve #2sintheta-3costheta=0#?
- How do you express #f(theta)=-6sin^2(theta)-3cos^2(theta)-2tan^4theta# in terms of non-exponential trigonometric functions?
- How do you solve #2cos^2(x)+ 4sin^2(x)=3#?
- How do you prove # (cosx - sinx)/(cos^3x - sin^3x) = 1/(tanxcos^2x + 1)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7